Distinct neural correlates of accuracy and bias in the perception of facial emotion expressions - Antypa, Despina; Kafetsios, Konstantinos; Simos, Panagiotis; Kyvelea, Marina; Kosteletou, Emmanouela; Maris, Thomas; Papadaki, Efrosini; Hess, Ursula (Social neuroscience, 2024)
We investigated neural correlates of Emotion Recognition Accuracy (ERA) using the Assessment of Contextualized Emotions (ACE). ACE infuses context by presenting emotion expressions in a naturalistic group setting and distinguishes between accurately perceiving intended emotions (signal), and bias due to perceiving additional, secondary emotions (noise). This social perception process is argued to induce perspective taking in addition to pattern matching in ERA. Thirty participants were presented with an fMRI-compatible adaptation of the ACE consisting of blocks of neutral and emotional faces in single and group-embedded settings. Participants rated the central character's expressions categorically or using scalar scales in consequent fMRI scans. Distinct brain activations were associated with the perception of emotional vs. neutral faces in the four conditions. Moreover, accuracy and bias scores from the original ACE task performed on another day were associated with brain activation during the scalar (vs. categorical) condition for emotional (vs. neutral) faces embedded in group. These findings suggest distinct cognitive mechanisms linked to each type of emotional rating and highlight the importance of considering cognitive bias in the assessment of social emotion perception.
Keywords: rozpoznání obličeje; Social Perception; zkreslení výsledků (epidemiologie); accuracy; fMRI; Brain Mapping; Bias; mužské pohlaví; mozek; Facial Recognition; Adult; mladý dospělý; bias; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Brain; Young Adult; ženské pohlaví; Humans; mapování mozku; světelná stimulace; emoce; social; Facial Expression; Emotion perception; Emotions; Photic Stimulation; dospělí; Female; sociální percepce; výraz obličeje; lidé; Male